MANAGEMENT OF EMPOWERMENT OF SIDEWALK TRADERS IN WEST DENPASAR SUB DISTRICT DENPASAR CITY: IN THE PERSPECTIVE OF CULTURAL STUDIES - Wana Pariartha, I Wayan; Suastika, I Made; Mariyah, Emiliana; Sudibia, I Ketut (E-Journal of Cultural Studies, 2012)
Sidewalk traders, as informal economic sector, have been in existence in almost allthe cities in Indonesia. As an impact of migration of people, they have been recognized as astructural phenomenon which will always exist. They will always exist in Denpasar City. InWest Denpasar Sub District, as part of Denpasar City, their existence has been assumed notonly to cause the city to look disorganized but it has also been assumed to create discomfortand to disturb public order. However, as Indonesian citizens, they have the right to haveoccupation and live properly as stated in Article 27 of the 1945 Constitution. Theempowerment management of the sidewalk traders in West Denpasar Sub District refers tothe Local Rules and Regulations (Perda) of number 3 of Year 2000. However, the fact inthe field shows that what has been expected has not been properly coming true yet.Based on this fact, a research was conducted with the problems formulated asfollows: 1) how the government managed the empowerment of the sidewalk traders; 2)what responses were given by the community to the model of such a management ofempowerment; 3) and what were its effects and meanings. As a consequence, this researchaims at 1) identifying the management of empowerment of the sidewalk traders; 2)identifying the responses given by the community to the model of such a management ofempowerment; 3) identifying its effects and meanings. From the aspect of methodology,this research is classified as a qualitative one. The theory of deconstruction, the theory ofhegemony, the theory of response, the theory of motivation and achievement wereemployed for exploring the problems formulated above. The techniques employed forcollecting the data needed were the technique of observation, the technique of interview,the technique of observation and focus discussion group.The findings show that the Local Rules and Regulations (Perda) of Number 3 of2000, which is derived from the Local Rules and Regulations (Perda) of Number 15 ofYear 1993, which is used as the reference of how such a management of empowerment isconducted, does not accommodate the problems related to the sidewalk traders. In fact, ithas been implemented by the government in the following three ways; (1) through the subdistrict governmental agencies; (2) through direct supervision of the municipal, sub district,administrative village and neighborhood governmental agencies; (3) through traditionalvillages (desa pekraman/adat).The responses given by the community varied. The responses given by thecommunity of consumers were negative resulting from lack of socialization. The responsesgiven by the sidewalk traders were negative as well. However, socially, economically and
Keywords: politically, the empowerment management of the sidewalk traders gave positive and negative impacts. And the meanings given by such a management of empowerment were related to solidarity, well being and psychology. Based on the findings of the research, a